Formation of Student Character in Islamic Religious Education - Zubairi Muzakki; Nurdin Nurdin (LP. Ma'arif Janggan Magetan, 2022)
Schools or madrasas are one of the places that provide teaching on Aqidah Akhlak and Islamic religious education, so it is appropriate for madrasas or schools to provide facilities in the form of learning media/learning media that support teaching and learning activities, of course with the hope that what is the basic goal of learning can be achieved. This subject seeks to create quality human resources (HR) not only in cognitive aspects but also in affective and psycho-motor aspects based on Islamic religious values. The type of research used is library research. While the data obtained is a descriptive narrative of student's character building. The research includes that learning Aqidah Akhlak and Islamic religious education is a very important factor for students. So students get good learning in madrasas, with good methods, supporting facilities and infrastructure in the form of learning media/learning media used, of course this is an aspect that supports student success in forming themselves with Islamic character. While parents have full responsibility for everything related to students, parents are responsible for the child's future, so they are required to provide positive education, including by cultivating their potential and need to emphasize early on so that results will be achieved. the maximum. Parents' responsibility can also be increased by giving homework, namely work given by the teacher that students must do at home. With the involvement of third parties, communication is established, especially with parents and family. In this case the expected input is communication with parents as well as parental control over their children.